2015
DOI: 10.1039/c5cp03910j
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme adsorption at a silica surface using simulation and experiment: effects of pH on protein layer structure

Abstract: a Hen Egg White Lysozyme (HEWL) is a widely used exemplar to study protein adsorption on surfaces and interfaces. Here we use fully atomistic Molecular Dynamics (MD) simulations, Multi-Parametric Surface Plasmon Resonance (MP-SPR), contact angle and zeta potential measurements to study HEWL adsorption at a silica surface. The simulations provide a detailed description of the adsorption mechanism and indicate that at pH7 the main adsorption driving force is electrostatics, supplemented by weaker hydrophobic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 41 publications
9
91
0
Order By: Relevance
“…The associated zeta potentials were calculated using Henry's equation, [3], and displayed in Figure 3. The zeta potential curve for Lysozyme in a solution with ionic strength I = 1 x 10 -2 M compares well with previously published results 33 .The isoelectric point of Lysozyme in this case is approximately 10.0, in agreement with previous results 26 . In the case of lysozyme AuNC nucleation dramatically changes the zeta potential.…”
Section: Resultssupporting
confidence: 92%
“…The associated zeta potentials were calculated using Henry's equation, [3], and displayed in Figure 3. The zeta potential curve for Lysozyme in a solution with ionic strength I = 1 x 10 -2 M compares well with previously published results 33 .The isoelectric point of Lysozyme in this case is approximately 10.0, in agreement with previous results 26 . In the case of lysozyme AuNC nucleation dramatically changes the zeta potential.…”
Section: Resultssupporting
confidence: 92%
“…51 The orientation predicted by our model for lysozyme at its isoelectric point (pH 11.2) on a negative surface is very close to the most stable orientation predicted by these MD simulations. [49][50][51][52] Moreover, MD studies have identified the same aminoacids as our study (Lys1, Arg5, Arg125 and Arg128) as the aminoacids that reside closest to the surface and contribute the most to the interaction with the silica substrate.…”
Section: Analysis Of Lysozyme-surface Interactionsupporting
confidence: 67%
“…Well-designed simulations can show not only how proteins adsorb to different surfaces, but also provide understanding of what the driving forces are and how they can be controlled through surface chemistry, and how bio-activity can be preserved by retaining the protein secondary and tertiary structures. There is growing consensus that the orientation of the protein at the surface is paramount, and that this depends on the surface chemistry [11][12][13][14][15] . Of particular note is the idea that electric fields above charged surfaces will play a crucial role in steering the protein during adsorption, and so determine protein orientation once adsorbed [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…There is growing consensus that the orientation of the protein at the surface is paramount, and that this depends on the surface chemistry [11][12][13][14][15] . Of particular note is the idea that electric fields above charged surfaces will play a crucial role in steering the protein during adsorption, and so determine protein orientation once adsorbed [14][15][16] . Provided that any unfolding induced by interactions with the surface are of limited extent, this provides the means to engineer surface functionalization through controlled protein adsorption 12 .…”
Section: Introductionmentioning
confidence: 99%